PENYISIHAN TIMBAL (Pb) DARI TANAH TERKONTAMINASI DENGAN PROSES ELEKTROMIGRASI - purwanta, wahyu (Center for Environmental Technology - Agency for Assessment and Application of Technology, 2005)
This study is trying to apply a new method in remediation electrokinetic byinserting conductive solution between cathode and soil to be treated. This is purposed in keeping the pH in low condition and preventing the precipitation of heavy metals in the soil adjacent to the cathode that often happen in the previous electrokinetic methods. Concentration of Pb (C0), period (t), concentration of conductive solution were selected as parameters, both with artificially contaminated sand and naturally contaminated soil experiments. The experiment with natural soil C0 = 975 ppm gave lower efficiency at 32,84% when it compares with sand as the medium, with the experiment in the same condition at 87,68%. Concentration of KCl also influenced theperformance of system which was shown by the increasing in removal efficiency. The double increase of conductive solution concentration does not proportionally increase the flux of Pb. Although desorption in the natural soil take time longer than in the sand the removal efficiency relatively low. This is caused by the immobile state of Pb in the natural soil and the complexity of chemical reaction between heavy metals with surface of soil particle.